Design and Assessment of Convolutional Neural Network Based Methods for Vitiligo Diagnosis - Zhang, Li; Mishra, Suraj; Zhang, Tianyu; Zhang, Yue; Zhang, Duo; Lv, Yalin; Lv, Mingsong; Guan, Nan; Hu, Xiaobo Sharon; Chen, Danny Ziyi; Han, Xiuping (Frontiers in Medicine, 2021)
Background: Today’s machine-learning based dermatologic research has largely focused on pigmented/nonpigmented lesions concerning skin cancers. However, studies on machine-learning-aided diagnosis of depigmented nonmelanocytic lesions, which are more difficult to diagnose by unaided eye, are very few. Objective: We aim to assess the performance of deep learning methods for diagnosing vitiligo by deploying Convolutional Neural Networks (CNNs) and comparing their diagnosis accuracy with that of human raters with different levels of experience. Methods: A Chinese in-house dataset (2876 images) and a world-wide public dataset (1341 images) containing vitiligo and other depigmented/hypopigmented lesions were constructed. Three CNN models were trained on close-up images in both datasets. The results by the CNNs were compared with those by 14 human raters from 4 groups: expert raters (>10 years of experience), intermediate raters (5-10 years), dermatology residents, and general practitioners. F1 score, the area under the receiver operating characteristic curve (AUC), specificity, and sensitivity metrics were used to compare the performance of the CNNs with that of the raters. Results: For the in-house dataset, CNNs achieved a comparable F1 score (mean [standard deviation]) with expert raters (0.8864 [0.005] vs 0.8933 [0.044]) and outperformed intermediate raters (0.7603 [0.029]), dermatology residents (0.6161 [0.068]) and general practitioners (0.4964 [0.139]). For the public dataset, CNNs achieved a higher F1 score (0.9684 [0.005]) compared to the diagnosis of expert raters (0.9221 [0.031]). Conclusion: Properly designed and trained CNNs are able to diagnose vitiligo without the aid of Wood’s lamp images and outperform human raters in an experimental setting.